2016
DOI: 10.4187/respcare.04034
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as a Predictor of In-Hospital Mortality After Exacerbation of COPD

Abstract: BACKGROUND: COPD is associated with cardiovascular and renal dysfunction. Cystatin C (CysC) is a biomarker of renal function and an independent risk factor for all-cause and cardiovascular mortality among elderly persons. The aim of the study was to examine the prognostic role of CysC for in-hospital mortality in subjects with a COPD exacerbation. METHODS: Upon admission, serum CysC levels and arterial blood gas analysis from 477 subjects with a COPD exacerbation were measured. Clinical characteristics were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Consistent with previous studies, we found that the elevated levels of Cys C were significantly correlated with disease status and lung function. Hu et al [24] found that the elevated Cys C levels was an important and independent risk factor of increased mortality in a hospital setting during COPD exacerbation, Formiga et al [51] indicated that inspiratory muscle function was reduced with greater degrees of inflammation in COPD as expressed higher levels of Cys C. Combining with the results of previous studies and this meta-analysis, we thought that the elevated levels of serum Cys C might indicate the exacerbation and progression of COPD.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Consistent with previous studies, we found that the elevated levels of Cys C were significantly correlated with disease status and lung function. Hu et al [24] found that the elevated Cys C levels was an important and independent risk factor of increased mortality in a hospital setting during COPD exacerbation, Formiga et al [51] indicated that inspiratory muscle function was reduced with greater degrees of inflammation in COPD as expressed higher levels of Cys C. Combining with the results of previous studies and this meta-analysis, we thought that the elevated levels of serum Cys C might indicate the exacerbation and progression of COPD.…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies indicate a possible link between Cys C and COPD [24][25][26][27][28]; however, the conclusion is not clear. Most studies have shown that serum Cys C levels are higher in the exacerbation group than stable COPD or healthy control [29,30], but Selder et al [31] find that serum Cys C levels are lower in exacerbation group than stable COPD.…”
Section: Introductionmentioning
confidence: 96%
“…Of course, there are also studies that showed that elevated HsCRP was not associated with mortality of AECOPD 26. In a previous study from our group, we showed that plasma cystatin C was a risk factor for in-hospital mortality 27. Additionally, in another study from our group, the PSI index was associated with in-hospital death 28.…”
Section: Discussionmentioning
confidence: 57%
“…Cystatin C is easily detectable in the biological fluids and acts as a reliable marker, independently of age, sex, and muscle mass [ 27 29 ]. Previous studies not only confirmed the role of cystatin C in indicating organ dysfunction but also clarified that serum cystatin C levels might associate with inflammatory phase and adverse outcomes in various diseases [ 30 – 33 ]. These findings accorded with our observations of cystatin C levels and COVID-19.…”
Section: Discussionmentioning
confidence: 93%